The comparative analysis of judicial practice in the EU Member-States and the European Court of Justice in questions of liability imposition within the infringement of intellectual property rights - Михайлюк, Галина Олегівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2013)
The European Convention on Human Rights in article 1 Protocol 1 provides property rights protection asone of the main rights covered by the determination of international human rights protection. The recentnational court decisions of the Member States and their correlation with the corresponding ECJ’s decisions, legislative EU database as to the protection of trademark proprietors’ rights in advertising through the Internethave been analyzed in the article.